Extension-Worker Communication Strategy Using Islamic Education During the Covid 19 Pandemic - M Djakfar Hasbi; Lahmuddin Lubis; Ahmad Tamrin Sikumbang (Edukasi Islami : Jurnal Pendidikan Islam, 2022)
Islamic Extension-Workers work for the Ministry of Religion of the Republic of Indonesia to provide religious counseling to Indonesians. They have actively promoted Da'wah Islamiyah through taklim, religious talks, and other activities. After the COVID-19 pandemic hit Indonesia in early March 2020, religious development initiatives shifted. To stop the spread of COVID-19, large crowd-drawing events were banned.This study addresses how Islamic religious teachers can communicate religious development through Islamic education during the COVID-19 epidemic. This study takes a qualitative approach. The qualitative research topic is sociological in nature. This study used observation, interviews, and documentation. This study examined data reduction, display, and conclusion.During the COVID-19 pandemic, Islamic Extension-Workers advised on the above specialities and communicated government policy and debated COVID-19. Islamic Extension Workers coach religiously after building a communication strategy. Strategy is implemented. Coaching religion extended communication planning: Islamic education through regular Islamic studies, Covid Task Force engagement, report and evaluate.Communication planning for Islamic Extension-Workers in North Aceh District's religious expansion lacks SWOT Analysis and other current management practices. Islamic Extension-Workers were not informed of the Vision and Mission decrease. `The Ministry of Religion of the Republic of Indonesia is expected to support the Regional Office of the Ministry of Religion of North Aceh Regency build internet connection facilities to improve religious development between extension workers and clients/communities.